Pharmacology Curriculum and Teaching Methods: A Comparative Study Between Two Nursing Programs in A Nepalese College - Sharma, Manoj; Kafle, Kumud Kumar (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Pharmacology is one of the basic science subjects included in graduate nursing programs (B. Sc Nursing and Bachelor of Science in Nursing) under Tribhuvan University. Both these programs are being run at our institute. This article describes the evaluation of pharmacology course and teaching methodology at our institute by B. Sc Nursing (B. Sc) and Bachelor of Science in Nursing (BNS) students and also compares students’ views between these two nursing programs to facilitate pedagogical learning. Methods: At the end of the course of 2071-2072 BS academic year of first year nursing students of B. Sc and BNS programs, a structured teaching evaluation questionnaire was designed to obtain students’ view on pharmacology curriculum and lectures. Yates corrected Chi square test was applied whenever necessary and p value considered significant at less than or equal to 0.05. Results: Only 37% B. Sc and 60% BNS students responded that the lecture content was in accordance with the curriculum. Only 52% BNS and 97% B. Sc students found the course content to be relevant and useful. 68% BNS students responded that they have felt a lot improvement in their understanding of pharmacology subject as compared to just 23% of B. Sc students. Majority of the students preferred the LCD mode of presentation. Conclusion: There were minor differences found between opinions of two sets of students. Major need for improvement areas suggested in curriculum were course content not being clear and the objectives being ill defined. Similarly, in relation to facilitator, they have recommended to improve voice clarity.